Worldwide complexity of weeds - Pacanoski, Zvonko; Mehmeti, Arben (Acta herbologica, 2022)
No more than 3% of the total plant species on the Earth account weeds, but they cause huge difficulties to humankind by intrusive in food security and safety, health, environment, economic stability, and welfare. The problem of weeds as a worldwide problem increases, as human activities and their interference with the environment are increasing. Weeds by advantage of their forceful and flexible nature cause considerable losses in the agriculture, forestry, aquaculture, water supply and a host of other human enterprises. Overall, weed-crop competition is a most important reason reducing sustainable crop production. They decrease production because of competition, allelopathy, and by ensuring environments for pathogens in consequence using them as alternating host for numerous insects and fungi and cause rising harvesting expenditures. Weeds are prominent yield reducers that are in numerous conditions economically more significant than insects, pathogens or other biotic constrains together. Worldwide damages generated by weeds are responsible for a loss of 13.2% of crops yield, but the probable loss of agriculture production without weed control was predicted from 20 to 90% globally.
Keywords: weeds, control, damages, losses, costs